Flood vulnerability and food security in eastern India: A threat to the achievement of the Sustainable Development Goals. (December 2021) - Sam, Anu Susan; Abbas, Azhar; Surendran Padmaja, Subash; Raghavan Sathyan, Archana; Vijayan, Dhanya; Kächele, Harald; Kumar, Ranjit; Müller, Klaus
Abstract: The food security situation in India has improved due to economic growth, increased agricultural productivity, public policies and hunger eradication programmes. Nevertheless, much of India's population still suffers from hunger and poverty. Floods obstruct agricultural production; destroy infrastructure; and disrupt livelihoods, normal services, health care, etc. In this way, floods ultimately affect households' food security. We examined household food security in flood-prone rural areas of India in a more extensive way than in previous studies by constructing an index that incorporates various factors of the food security dimensions. Factors determining the level of flood-prone households' food security were also analyzed. By polychoric principal component analysis, an aggregate food security index was constructed. The food security score was regressed on different explanatory variables to evaluate their effect on the overall food security situation in the study area. Our results showed that three-fourths of the respondent households faced food security issues to varying degrees. Family type, physical assets and employment scheme showed positive impacts on the level of food security of the respondents. In contrast, households with female household heads and those suffering losses of property due to floods were adversely affected in terms of negative impacts on overall food security. The results suggest the need for the adoption of integrated strategies to effectively address food security issues amidst the increased severity of flood events. The study findings are useful for policy makers in India and countries with similar backgrounds to tackle the food insecurity brought about by flood hazards. Graphical abstract: Image 1 Highlights: Flood impedes agricultural production and disrupts livelihoods which ultimately affects the food security of households. Development of food security index by incorporating various dimensions of food security. A new framework is created by linking the FAO dimensions of food security with the IPCC dimensions of climate change. This study provides information on the base level indicators that are leading to food security.